Serum protease inhibitor - Ulinastatin in the complex therapy of severe acute pancreatitis complicated by sepsis (Eurasian Research Bulletin, 2022)
Acute pancreatitis is an acute inflammation of the pancreas that often leads to pancreatic necrosis and is the cause of death in 40% to 70% of patients. [1] Given the severity of this disease and the insufficient effectiveness of generally accepted methods of treatment, we studied the effectiveness of the drug Ulinastatin (serum protease inhibitor) in the complex therapy of acute pancreatic necrosis, complicated by diffuse purulent peritonitis and sepsis.